2021
DOI: 10.1016/j.compbiomed.2021.104662
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential human and medicinal plant microRNAs against SARS-CoV-2 3′UTR region: A computational genomics assessment

Abstract: The coronavirus disease of 2019 (COVID-19) began as an outbreak and has taken a toll on human lives. The current pandemic requires scientific attention; hence we designed a systematic computational workflow to identify the cellular microRNAs (miRNAs) from human host possessing the capability to target and silence 3'UTR of SARS-CoV-2 genome. Based on this viewpoint, we extended our miRNA search to medicinal plants like Ocimum tenuiflorum , Zingiber officinale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“… ( McDonald et al, 2021a ) hsa-miR-1236–3p, zof-miR2673b Bioinformatics ‘GGAAGAG’ in 5024 SARS-CoV-2 3′UTR The target of these microRNAs represents a region concentrated in the SARS CoV 2 genome that may become a promising target for the fight against COVID 19. ( Mangukia et al, 2021 ) miR-200c In vitro Neonatal rat cardiomyocytes (NRCMs) and Neonatal rat cardiac fibroblasts (NRCFs) ACE2 MiR-200c modulates ACE2 expression in both rat and human cardiomyocytes, which can be used to treat cardiovascular complications of COVID-19. ( Lu et al, 2020 ) miR-155, miR-130a Clinical Recovered COVID-19 patients and healthy 70 Blood samples miR-155 and miR-130a levels were higher in the mild/moderate group compared to the severe/critical ( Li et al, 2021 ) hsa-miR-15b-5p, hsa-miR-195-5p, hsa-miR-221-3p, hsa-miR-140-3p, and hsa-miR-422a In vitro and bioinformatics Hamster lung tissues hsa-miR-15b-5p, hsa-miR-140-3p, and hsa-miR-422a have been decreased, and hsa-miR-195-5p and hsa-miR-221-3p have been increased in affected specimens.…”
Section: Dysregulated Mirnas In Covid-19mentioning
confidence: 99%
“… ( McDonald et al, 2021a ) hsa-miR-1236–3p, zof-miR2673b Bioinformatics ‘GGAAGAG’ in 5024 SARS-CoV-2 3′UTR The target of these microRNAs represents a region concentrated in the SARS CoV 2 genome that may become a promising target for the fight against COVID 19. ( Mangukia et al, 2021 ) miR-200c In vitro Neonatal rat cardiomyocytes (NRCMs) and Neonatal rat cardiac fibroblasts (NRCFs) ACE2 MiR-200c modulates ACE2 expression in both rat and human cardiomyocytes, which can be used to treat cardiovascular complications of COVID-19. ( Lu et al, 2020 ) miR-155, miR-130a Clinical Recovered COVID-19 patients and healthy 70 Blood samples miR-155 and miR-130a levels were higher in the mild/moderate group compared to the severe/critical ( Li et al, 2021 ) hsa-miR-15b-5p, hsa-miR-195-5p, hsa-miR-221-3p, hsa-miR-140-3p, and hsa-miR-422a In vitro and bioinformatics Hamster lung tissues hsa-miR-15b-5p, hsa-miR-140-3p, and hsa-miR-422a have been decreased, and hsa-miR-195-5p and hsa-miR-221-3p have been increased in affected specimens.…”
Section: Dysregulated Mirnas In Covid-19mentioning
confidence: 99%
“…Upon abstract collection, 44 research papers (23 in silico [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and 21 experimental studies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]) met the inclusion criteria and were used for downstream analysis. The entire workflow of the current study is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Whilst five conserved plant miRNAs: miR-166, miR-169, miR-172, miR-390, and miR-399 that were very likely to align and interact onto the six HBV gene sequences [ 19 ]. A report from our study group also revealed a cross-species interaction of plant miRNAs belonging to the family of miR477 ubiquitously found in all three medicinal plant genomes of O. tenuiflorum , P. nigrum and Z. officinale to pinpoint a plausible role of plant derived dietary miRNAs to mediate viral mRNA silencing and provide antiviral defence against SARS-CoV-2 infection [ 23 ]. These are all amongst the evidence which suggest the conjecture of the inhibitory role of exogenous miRNAs being inhibitory for SARS-CoV-2 viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…A total of five plant miRNAs from three medicinal plants Ocimum tenuiflorum , Piper nigrum and Zingiber officinale were obtained having potential to align with the SARS-CoV-2 3′ UTR region. From a family of plant miRNAs, mir477 and miR2673 were identified to bind and regulate the expression of SARS-CoV-2 viral mRNA using in-silico approach [ 23 ].…”
Section: Introductionmentioning
confidence: 99%